2008
DOI: 10.1007/s11199-008-9518-z
|View full text |Cite
|
Sign up to set email alerts
|

Academic Success of Mexican Origin Adolescent Boys and Girls: The Role of Mothers’ and Fathers’ Parenting and Cultural Orientation

Abstract: To understand the role that Mexican origin parents play in their children’s academic success, this study used structural equation modeling to evaluate the associations of parents’ parenting practices (warmth, monitoring, harshness, and academic involvement) and cultural orientations (enculturation and acculturation) with their adolescents’ grades, classroom behavior, and association with peers who get into trouble at school. Data were obtained from teachers, mothers, fathers, and male and female adolescents in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
79
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(91 citation statements)
references
References 42 publications
6
79
0
6
Order By: Relevance
“…More recently, however, research on fathers has explored the relationship between paternal parenting practices and child development. Evidence increasingly suggests that mothers and fathers independently shape areas of child development, such as academic success 20 and peer relationships. 21 Little is known about how paternal parenting processes are associated with adolescent sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, however, research on fathers has explored the relationship between paternal parenting practices and child development. Evidence increasingly suggests that mothers and fathers independently shape areas of child development, such as academic success 20 and peer relationships. 21 Little is known about how paternal parenting processes are associated with adolescent sexual behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Family obligations have been associated with Latino/a youth's greater school engagement and higher postsecondary education (Fuligni 2001;Tseng 2004), especially for students who perform more poorly in school (Fuligni and Pederson 2002). Similarly, Mexican behavioral and linguistic orientations among mothers have been associated with adolescent girls' getting higher grade point averages in school (Dumka et al 2009). On the other hand, Latino/a cultural orientations can interfere with Mexican-origin youth's educational attainment.…”
Section: Cultural Orientations and Adolescent Academic Successmentioning
confidence: 99%
“…Of course, this may also reflect differences in the specific types of family conflict involved. Updegraff et al (2009) reported that fatheradolescent conflict affected risk-taking by Mexican immigrant females more than males in one study whereas parental harshness was associated with classroom misbehaviour by adolescent boys of Mexican origin and maternal harshness with problematic peer relationships yet better school performance by girls in another study (Dumka et al 2009). By contrast, Qin (2009) reported no salient gender differences in the reactions to immigration by Chinese boys and girls, suggesting that these patterns are not characteristic of all immigrants groups or at all points after migration.…”
mentioning
confidence: 98%